2004
DOI: 10.1523/jneurosci.1486-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Step Training-Dependent Plasticity in Spinal Cutaneous Pathways

Abstract: Plasticity after spinal cord injury can be initiated by specific patterns of sensory feedback, leading to a reorganization of spinal networks. For example, proprioceptive feedback from limb loading during the stance phase is crucial for the recovery of stepping in spinal-injured animals and humans. Our recent results showed that step training modified transmission from group I afferents of extensors in spinal cats. However, cutaneous afferents are also activated during locomotion and are necessary for proper f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 87 publications
1
52
0
Order By: Relevance
“…Possible mechanisms subserving the permissive action of treadmill training in the re-expression of hindlimb locomotion remain mostly unknown despite recent progress (de Leon et al, 1999;Tillakaratne et al, 2002;Cote et al, 2003;Cote and Gossard, 2004;Ying et al, 2005). The present work provides functional evidence that treadmill training shapes spinal plasticity after partial lesions.…”
Section: Treadmill Training Promotes Spinal Plasticitymentioning
confidence: 53%
See 1 more Smart Citation
“…Possible mechanisms subserving the permissive action of treadmill training in the re-expression of hindlimb locomotion remain mostly unknown despite recent progress (de Leon et al, 1999;Tillakaratne et al, 2002;Cote et al, 2003;Cote and Gossard, 2004;Ying et al, 2005). The present work provides functional evidence that treadmill training shapes spinal plasticity after partial lesions.…”
Section: Treadmill Training Promotes Spinal Plasticitymentioning
confidence: 53%
“…For instance, hindlimb locomotion after complete and incomplete spinal lesions is increasingly dependent on the proper integration of sensory afferent inputs Steeves, 1995, 1997;Bouyer and Rossignol, 2003) and it has been proposed that a normalization of these inputs is required for the expression of spinal stepping (Cote et al, 2003;Cote and Gossard, 2004). However, changes in neuronal and synaptic properties (Heckmann et al, 2005) and in neuromodulatory systems intrinsic to the spinal cord (de Leon et al, 1999;Giroux et al, 1999Giroux et al, , 2003Chau et al, 2002;Edgerton et al, 1997;Tillakaratne et al, 2002), are undoubtedly also involved.…”
Section: Reorganization Of the Spinal Locomotor Network After Partialmentioning
confidence: 99%
“…For example, the amplitude of Group Ia fiber-evoked monosynaptic EPSPs (sEPSPs) was higher in trained than non-trained rats that were spinally transected as neonates. Cote and Gossard (2004) reported a reduction in Ia-evoked EPSPs in trained adult spinal cats, but enhanced cutaneous reflexes in trained compared to non-trained spinal cats when stimulating afferents that were thought to be activated during weight-bearing stepping. They also observed that the Group Ib (Golgi tendon organ) disynaptic input to homonymous motoneurons was reversed from inhibition to excitation more frequently in trained than in nontrained cats (Cote et al, 2003).…”
Section: Neurophysiological Plasticity In Response To Trainingmentioning
confidence: 97%
“…Given that neither changes in muscle properties (Roy and Acosta, 1986;Roy et al, 1998Roy et al, , 1999 nor regeneration of descending tracts (Joynes et al, 1999;Grillner, 2002) could account for the differences in stepping ability after training, these improvements must stem from plasticity of neurons and circuits involved in stepping that are present in the lumbar spinal cord (Grillner, 2002). Little is known, however, about how the spinal circuitry changes in response to training and how specific changes may contribute to the improved motor performance (Cote et al, 2003;Cote and Gossard, 2004).…”
Section: Introductionmentioning
confidence: 99%